PENINGKATAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MODEL PROBLEM BASED LEARNING (PBL) DI KELAS IV SEKOLAH DASAR - Taufik Hidayat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The study aims to describe the implementation of the Problem Based Learning (PBL) model to improve learning outcomes on the material of reproduction and the distribution of the number of frogs in the fourth grade of elementary school. This type of research is Class Action Research (PTK) using both qualitative and quantitative approaches. The subject of the study was 17 students in Class IV SD N 06 Kubu. The results show an improvement. In Cycle I meeting the observation of the teaching module from 95.8% to 100% in cycle I meetings II. Implementation on the teachers and students aspects of cycles I meeting I 85.7% went 96.4% in Cycle II meeting I. Average evaluation of learning outcomes of the participants in the I cycle 66.41% to 86.11% in the cycle II meetings I.